2018
DOI: 10.1002/chem.201804215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Liquid‐Crystalline Tetraoxapentacene Derivatives Exhibiting Aggregation‐Induced Emission

Abstract: A series of new tetrakis(dialkoxyphenyl) dicyanotetraoxapentacene derivatives (1 a–c) were prepared by reaction of the appropriate terphenyl diols with tetrafluoroterephthalonitrile in good yields. Compounds 1 b and 1 c, which bear hexyloxy and decyloxy side chains, exhibited columnar hexagonal mesophases, as shown by polarized optical microscopy, variable‐temperature powder X‐ray diffraction, and differential scanning calorimetry. Single‐crystal X‐ray diffraction of methoxy‐substituted 1 a revealed that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…This motif has been used for the preparation of rigid, macromolecular networks such as polymers with intrinsic microporosity, covalent organic frameworks, , as well as cyclodextrin-based polymers for wastewater treatment. , In these examples, the DCTOP moiety serves primarily as a rigid linker. Recently, we showed that dialkoxyphenyl DCTOP derivatives exhibit columnar mesophases and have aggregation-induced emission . Given the interesting properties of these materials, their similarity to heteroacenes, and their potential as luminescent dyes, there is an interest in exploring this synthetic approach for the preparation of other heteroacene analogues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This motif has been used for the preparation of rigid, macromolecular networks such as polymers with intrinsic microporosity, covalent organic frameworks, , as well as cyclodextrin-based polymers for wastewater treatment. , In these examples, the DCTOP moiety serves primarily as a rigid linker. Recently, we showed that dialkoxyphenyl DCTOP derivatives exhibit columnar mesophases and have aggregation-induced emission . Given the interesting properties of these materials, their similarity to heteroacenes, and their potential as luminescent dyes, there is an interest in exploring this synthetic approach for the preparation of other heteroacene analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that dialkoxyphenyl DCTOP derivatives exhibit columnar mesophases and have aggregationinduced emission. 18 Given the interesting properties of these materials, their similarity to heteroacenes, and their potential as luminescent dyes, there is an interest in exploring this synthetic approach for the preparation of other heteroacene analogues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our previous studies focused on nucleophilic substitution reactions of bidentate nucleophiles with tetrafluoroterephthalonitrile to furnish a series of heteropentacene analogues, where the solid state structures and crystal packing of these compounds were described. , Using this methodology, compounds 1 – 6 were conveniently accessed via nucleophilic aromatic substitution of a fluorinated arene with either catechol or a 2-aminophenol derivative.…”
Section: Resultsmentioning
confidence: 99%
“…This often leads to better defined intermolecular interactions and allows for the adjustment of optoelectronic properties, such as fluorescence and charge transport. [36,45,46] Several unusual columnar mesophase structures have been reported for some of these board-shaped dyes and it is our intention to specifically highlight rare supramolecular structures and their underlying molecular structures. Concepts such as shape-anisotropy (aspect ratios), nanosegregation, and relative packing volumes were applied qualitatively to reason the formation of different types of columnar mesophase based on molecular design.…”
Section: Introductionmentioning
confidence: 99%